Cerium-induced changes in the π-band of graphene. Issue 115 (30th November 2016) - Kim, Jingul; Lee, Paengro; Ryu, Mintae; Park, Heemin; Chung, Jinwook
Abstract : By doping magnetic Ce atoms on a single layer graphene, we report a new and efficient means of modifying structural and electronic properties of graphene that opens a temperature-dependent band gap of size up to 0.5 eV. Abstract : Modifying or controlling the intrinsic properties of graphene, such as by controlling its band gap and carrying out spin injection of its π-electrons, have been a recent focus of research in graphene technology in order to promote the industrial applications of its superb properties. Here, we carried out photoemission spectroscopy experiments using synchrotron photons and showed several unique changes in the electronic and structural properties of graphene resulting from its adsorption of magnetic cerium (Ce) atoms. A band gap as large as E g = 0.50 eV opened when the Ce-adsorbed graphene was cooled to 41 K after a brief annealing at a temperature T a of 1200 °C. As the temperature of this sample was then increased to room temperature (RT), the size of the band gap decreased gradually to an E g of 0.36 eV, indicative of a temperature-dependent structural and/or spin-ordering phase transition. We also observed the presence of two different stages of Ce-intercalation upon annealing the graphene with Ce adsorbed at RT: the Ce atoms first intercalated below graphene at a T a of 530 °C and then below the buffer layer at a T a of 1050 °C. We discuss the physical implications of these temperature-dependent features of the Ce-adsorbed graphene.